From Infrastructure to Growth: Evaluating PPP Investments in Morocco Through the ARDL Model - Wissal Doua; Nouhaila Nouhaila; Mohammed Khariss; Mohammed Rachid Aasri (European Scientific Journal, ESJ, 2025)
This study investigates the impact of public–private partnerships (PPPs) on Morocco’s economic growth over the period 1993–2023. GDP growth is employed as the dependent variable, with the number of PPP projects, PPP investment, gross fixed capital formation, unemployment, and inflation as explanatory variables. Using the Autoregressive Distributed Lag (ARDL) technique, the analysis captures both short-run and long-run dynamics. Results indicate that in the long run, PPP investment exerts a positive and significant effect on GDP growth, whereas the number of PPP projects has a negative impact, suggesting that project proliferation without efficiency may hinder performance. In the short run, PPP projects contribute positively, while unemployment consistently reduces growth. Robustness tests confirm the absence of serial correlation, heteroskedasticity, and non-normality, while CUSUM and CUSUMQ verify model stability. These findings highlight that investment quality, rather than project frequency, is the key driver of Morocco’s long-run growth, underscoring the need for governance and efficiency-centered PPP strategies.